Pathology of colorectal neoplasia. Issue 3 (March 2017) - Carey, Frank
Abstract: Colorectal adenomas and cancers are common. Diagnosis and management of these lesions requires close clinicopathological correlation. This article emphasizes clinically important issues in management of adenomas, including serrated lesions, and early stage cancers removed by local excision. Pathological interpretation and staging of formal resection specimens is also discussed. The biology of colorectal cancer is emphasized, particularly reflecting the need for molecular analysis to guide adjuvant oncological treatment.